ANALYSIS OF THE STAGES IN THE DEVELOPMENT OF HARDWARE FIREWALLS FOR TELECOMMUNICATIONS NETWORKS - PEDYASH, VOLODYMYR; LEDOVSKYI, YEVHEN; TKACH, VOLODYMYR; NOVOCHYNSKYI, YEVHEN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This paper analyzes the evolution of hardware firewalls for telecommunication networks from simple packet filters of the 1980s to contemporary systems with artificial intelligence capabilities. The research examines six generations of firewalls, each representing a significant advancement in network security technology responding to emerging threats. First-generation firewalls implemented basic packet filtering based on IP addresses and ports but offered limited protection against complex attacks. Second-generation devices introduced stateful inspection, enhancing security by monitoring active network connections. The third generation, application-level gateways, expanded analysis to the application layer, enabling deeper traffic inspection and more granular security policies. Fourth-generation firewalls integrated intrusion detection and prevention systems (IDS/IPS), allowing identification and blocking of attack patterns in real-time. Next-Generation Firewalls (NGFW), representing the fifth generation, revolutionized network security with deep packet inspection, application identification regardless of ports used, and integration of multiple security functions including traditional packet filtering, intrusion prevention, antivirus protection, URL filtering, and user identification. The paper details the architecture and capabilities of NGFWs, which currently dominate the enterprise segment. The newest sixth generation incorporating artificial intelligence is also examined, highlighting its ability to autonomously analyze traffic, detect hidden patterns, and adapt to new attacks without manual updates. The authors discuss hardware implementation challenges for each generation, from general-purpose processors to specialized systems with multi-level architectures incorporating ASIC circuits, network processors, and specialized machine learning modules. The research concludes by identifying trends pointing toward enhanced AI technologies and stronger integration with other security systems to create a unified ecosystem for data protection.
Keywords: information security; firewalls; evolution; NGFW; artificial intelligence; network protection